A polymeric ionic liquid functionalized temperature-responsive composite membrane with tunable responsive behavior1. Issue 15 (21st April 2015) - Tang, Ying; Tang, Beibei; Wu, Peiyi
<x xml:space="preserve">Abstract</x> A temperature-responsive composite membrane with tunable responsive behavior was obtained by chemically grafting a PIL functionalized temperature-responsive copolymer onto the BPPO supporting membrane.